PENGARUH PARTISIPASI MASYARAKAT, LATAR BELAKANG INDIVIDU, LATAR BELAKANG POLITIK DAN PEMAHAMAN REGULASI ANGGOTA DPRD TERHADAP PERAN ANGGOTA DPRD DALAM PENGAWASAN KEUANGAN DAERAH KABUPATEN KUANTAN SINGINGI (Program Studi Akuntansi - Universitas Islam Kuantan Singingi, 2020)
Abstract The aims of this research are to know (1) The effect of society participation on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency (2) The effect of individual background on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency (3) The effect of political background on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency (4) The effect of comprehension of the regulations of assembly at regional (DPRD) members on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency. This type of research is causal research using a quantitative approach. The sample in this research used the nonprobability sample selection method, precisely the purposive sampling. The source of data in this research is primary data obtained from the results of questionnaires directly to respondents. Data were analyzed using multiple linear regression with a statistical program (SPSS 21), after the classical assumption test was fulfilled. The results of the research shows that (1) Society participation partially has a positive and significant effect on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency with a significance value of 0,013 < 0,05; (2) Individual background partially has a positive and significant effect on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency with a significance value of 0,001 < 0,05; (3) Political background partially has a positive and significant effect on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency with a significance value of 0,004 < 0,05; (4) Comprehension of the regulations of assembly at regional (DPRD) members partially has a positive and significant effect on the role of assembly at regional (DPRD) members in the supervision of regional finances in the Kuantan Singingi regency with a significance value of 0,005 < 0,05. Keywords : Society Participation, Individual Background, Political Background, Comprehension of the Regulations and Supervision of Regional Finances Abstrak Penelitian ini bertujuan untuk mengetahui (1) Pengaruh partisipasi masyarakat terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi (2) Pengaruh latar belakang individu terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi (3) Pengaruh latar belakang politik terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi (4) Pengaruh pemahaman regulasi anggota DPRD terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi. Jenis penelitian ini merupakan penelitian kausal dengan menggunakan pendekatan kuantitatif. Sampel dalam penelitian ini menggunakan metode pemilihan sampel nonprobabilitas tepatnya pemilihan sampel bertujuan. Sumber data dalam penelitian adalah data primer yang diperoleh dari hasil penyebaran kuesioner yang dibagikan lansung kepada responden. Data analisis dengan menggunakan regresi linier berganda dengan alat program statistik (SPSS 21), setelah diuji asumsi klasik terpenuhi. Hasil penelitian ini menunjukkan bahwa (1) Partisipasi masyarakat secara parsial berpengaruh positif dan signifikan terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi dengan nilai signifikansi 0,013 < 0,05; (2) Latar belakang individu secara parsial berpengaruh positif dan signifikan terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi dengan nilai signifikansi 0,001 < 0,05; (3) Latar belakang politik secara parsial berpengaruh positif dan signifikan terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi dengan nilai signifikansi 0,004 < 0,05; (4) Pemahaman regulasi anggota DPRD secara parsial berpengaruh positif dan signifikan terhadap peran anggota DPRD dalam pengawasan keuangan daerah Kabupaten Kuantan Singingi dengan nilai signifikansi 0,005 < 0,05. Kata Kunci : Partisipasi Masyarakat, Latar Belakang Individu, Latar Belakang Politik, Pemahaman Regulasi dan Pengawasan Keuangan Daerah